Tutoring For Children In The Village Of Danda Jaya To Overcome The Shortage Of Online Learning In Schools During The Covid-19 Pandemic - Arif Ganda Nugroho (Comment: an International Journal of Community Development, 2021)
The COVID-19 pandemic has had an impact on many parties, this condition has penetrated the world of education. The Danda Jaya village government is currently still implementing an online/online learning policy. The problem faced by children there when learning online is that the cellular network is less supportive so that children have difficulty accessing lessons and children's difficulties in understanding lessons because learning is not practiced directly. This community service is tutoring for students at each student's home by means of online/online during this pandemic period according to Circular Letter Number 15 of 2020 concerning Guidelines for Organizing Learning from Home in an Emergency Period of Covid-19 Spread. The children's response when participating in the tutoring work program was very good.